Diabetologia Croatica : medical scientific journal of the Vuk Vrhovac Institute University Clinic for Diabetes, Endocrinology and Metabolis Diseases, School of Medicine, University of Zagreb, Society for Diabetes and Metabolic Diseases of the Croatian Medical ... : journal of diabetes, endocrinology and metabolic diseases ([Vuk Vrhovac Institute], 2020)
Mrežne stranice znanstvenog časopisa s temama iz područja dijabetologije, endokrinologije i bolesti metabolizma.